P129 Diagnosing asthma in symptomatic children at age 11: evidence from a birth cohort study. (December 2018) - Murray, C; Drake, S; Foden, P; Lowe, L; Durrington, H; Custovic, A; Simpson, A
Abstract : Background: UK guidance for diagnosing childhood asthma has recently been published by NICE. Recommendations include diagnostic algorithms based on four dichotomised tests of lung function (FEV1 /FVC ratio <70% or lower limit of normal (LLN), bronchodilator reversibility [BDR]≥12%, FeNO ≥35 ppb, and PEFR variability). The algorithms are largely based on studies of adults so the suitability of the tests for diagnosing asthma in children is unknown. The diagnostic worth of FEV1 /FVC, BDR and FeNO for identifying asthma in children was assessed in a population-based birth cohort (Manchester Asthma and Allergy Study – MAAS). PEFR variability was not measured in this population. Methods: At age 11 we assessed study participants using validated questionnaires and lung function measurement. Spirometry and FeNO (NIOX chemiluminescence analyser, Sweden) was measured according to ATS/ERS guidelines. Children who had previously doctor-diagnosed asthma, wheezing in the preceding 12 months and current use of asthma treatment were defined as having asthma; children negative to all three features made up a non-asthmatic control group. Results: At age 11, 584 children had all 3 measurements; 173 were symptomatic and not on regular ICS. There were 43 children with asthma and 56 non-asthmatic controls; the remaining 67 were classed as indeterminate and excluded from the analysis. FeNO had good diagnostic properties (AUC: 0.82, 95% CI: 0.73–0.91); FEV1 /FVC had moderate and BDR had poor diagnostic properties (AUC: 0.64, 0.57, respectively). We used Youden's J statistic to estimate the best cut-off values for each test individually. Our results indicated that FeNO ≥15 ppb and FEV1 /FVC<89% performed better than the recommended thresholds in the published guidance for children. Conclusions: Of the three tests, FeNO showed the best ability to distinguish between those with and without childhood asthma at age 11. Our results suggest that the cut-off values used in the NICE algorithm are suboptimal for this age group. We propose that age adjusted values for FEV1 /FVC and FeNO would likely improve the diagnostic performance.